Analisis Kesiapan Implementasi Badan Layanan Umum Daerah Puskesmas Kota Semarang (Studi Kasus pada Puskesmas Ngesrep dan Bandarharjo) - Edlin Shufi Adam; Anneke Suparwati; Septo Pawelas Arso (Jurnal Kesehatan Masyarakat (Undip), 2017)
Community Health Center as a public service agencies on health are requied to provide excellent service to community. However, still not met society’s expectations due to complexity of flow budgeting. Implementation of the Local Public Service Agency (BLUD) is proposed solution for the problems with these flexibility to improve the service quality. All of Community Health Center in Semarang will Implement BLUD. The purpose of this study is to determine the readiness of the health center in BLUD  Implementation case study in health centers community Ngesrep and Bandarharjo. The approach of this research is a qualitative descriptive. Data of this research were collected by in-depth interviews. The main informants numbered 4 are head of the community health center and head of administration with the triangulans numbered 5, are the treasurer and technical staff at both community health center and escort team of BLUD from Semarang Health Departement. the result of this research, Ngesrep and Bandarharjo Community Health Center is not ready to implement BLUD. It seen from lack of educational competences and lack number of staff because have no administrative personnel to implement BLUD and lack of infrastructure. The documents and requirement available as well, targets to be BLUD are good enough. Lack of communication and coordination. Executor Characteristics has support enough. Environment of social, economics, and politics is good, but there has no governing policy to regulate BLUD in municipal level. Executor Disposition is good it seen from Community Health Center Commitment and positive staffs attitude towards BLUD, but understanding and involvement of staff towards BLUD is still lack. The research suggest is to improve the understanding and qualification of staff and addition of administrative personnel for implementation of BLUD. Increase the intensity information of BLUD, making BLUD technical regulations on municipal level and improve the communication and coordination between community health center and Semarang health department.